Concentration Analysis of Eurycoma Longijolia Using Principle Compenent Based Artificial Taste Sensor. - Abdullah, Mohd. Zaid; Ahmad, Mohd Noor; Md. Shakaff, Ali Yeon; Ismail, Zhari (2003)

(untitled)
Water extract of Eurycoma Longifolia (Tongkat Ali) were analysed by artificial-taste sensor Employing 4mm diameter and 20cm thickness lipid membrane technology.